Analisis Implementasi Strategi Dots (Directly Observed Treatment Short-Course) sebagai Pengendalian Tuberkulosis: Systematic Review - Rizka Dwiyovita; Martha Irene Kartasurya; Nurjazuli Nurjazuli (Malahayati Nursing Journal, 2023)
ABSTRACT Indonesia is one of the countries with the highest burden of TB in the world. The DOTS strategy has been applied to control TB disease, but the implementation of the DOTS strategy has not been optimal due to the obstacles that have arisen. To analyze the implementation of DOTS strategy as tuberculosis control. This research is a systematic literature review using indexed articles on Google Scholar, Science Direct, Pub Med, and Garuda. Articles were selected using PRISMA (Preferred Reporting Items for Systematic Review and Meta-Analyses). Analysis of article quality using the Critical Appraisal Skills Program (CASP). Eight articles were obtained that were in accordance with the research, indicating that the implementation of the DOTS strategy as tuberculosis control on political commitment in terms of funding, case detection, drug taking supervisor (PMO), as well as recording and reporting has not run optimally, while the drug distribution has been going well. Implementation of the DOTS strategy can run optimally by increasing cross-sectoral collaboration in tuberculosis control. Keywords: Directly Observed Treatment Short-Course Strategy, Qualitative, Tuberculosis Control.  ABSTRAK Indonesia menjadi salah satu negara yang memiliki beban tertinggi TB di Dunia. Telah diterapkan strategi DOTS untuk penanggulangan penyakit TB, akan tetapi implementasi strategi DOTS belum optimal disebabkan oleh adanya hambatan yang muncul. Untuk menganalisis implementasi strategi DOTS sebagai pengendalian tuberkulosis. Penelitian ini merupakan kajian pustaka sistematik dengan menggunakan artikel terindeks pada Google Scholar, Science Direct, Pub Med, dan Garuda. Artikel yang dipilih menggunakan PRISMA (Preferred Reporting Items for Systematic Review and Meta-Analyses). Analisis kualitas artikel menggunakan Critical Appraisal Skills Program (CASP). Diperoleh delapan artikel yang sesuai dengan penelitian, menunjukkan bahwa implementasi strategi DOTS sebagai pengendalian tuberkulosis pada komitmen politik dalam hal pendanaan, deteksi kasus, pengawas minum obat (PMO), serta pencatatan dan pelaporan belum berjalan optimal, sedangkan pada pendistribusian obat sudah berjalan baik. Implementasi strategi DOTS dapat berjalan optimal dengan meningkatkan kerjasama di lintas sektor dalam pengendalian tuberkulosis. Kata Kunci: Directly Observed Treatment Short-Course Strategy, Kualitatif, Pengendalian Tuberkulosis.